(untitled) (Research, Society and Development, 2022)
Human Papillomavirus (HPV) infection is the main precursor of cervical cancer. Pap Smear is the main diagnostic method of this neoplasm by cytological analysis, however presents a high rate of false-negative cases. This study aimed to verify if micronucleus (MN) frequency test and the Fourier Transform Infrared (FTIR) Spectroscopy analysis may be alternative useful techniques to detect HPV in cervical fluid. Fifty samples with normal cytology obtained from patients after cytopathological examination were divided into two groups based on the presence or absence of HPV by previous analysis of molecular biology. Of the fifty samples analyzed, 46% showed the presence of MN in the cells. The frequency of MN observed was higher in the samples with HPV positive and was related with age, use of oral contraceptives and use of alcoholic beverages (p <0.001). FTIR analysis spectra showed high peak DNA and proteins in samples with a high frequency of MN (1170cm-1; 1516cm-1; 1404cm-1; 1473cm-1) compared with samples with absence of MN, probably due to chromosomal histones and MN constituents. However, no statistically significant difference was observed between these groups considering that the FTIR is a screening test and not specific. Thus, by the FTIR technique it was not possible to classify the samples by the spectral differences presented. The MN test can be considered a screening test for the detection of HPV, being possible to use it in clinical practice because it is a practical, simple, low-cost and non-invasive method. However, it is important to carry out studies in larger sample groups to investigate the application of the MN test and FTIR spectroscopy in the diagnosis of this infection and in the application in the prevention of cervical cancer.